The Incidence of Paediatric Acute Kidney Injury Identified Using an AKI E-Alert Algorithm in Six English Hospitals - Bhojani, Sheetal; Stojanovic, Jelena; Melhem, Nabil; Maxwell, Heather; Houtman, Peter; Hall, Angela; Singh, Cheentan; Hayes, Wesley; Lennon, Rachel; Sinha, Manish D.; Milford, David V.; , British Association for Paediatric Nephrology (Frontiers in Pediatrics, 2020)
Abstract Objective: Acute kidney injury (AKI) is a significant cause of morbidity and mortality among hospitalised patients. The objectives in this study were (i) to investigate the incidence of AKI using the National Health Services (NHS) AKI e-alert algorithm as a means of identifying AKI; and (ii) in a randomly selected sub-group of children with AKI identified using the algorithm, to evaluate the recognition and management of AKI. Patients and Methods: Retrospective cross-sectional study with initial electronic retrieval of creatinine measurements at six hospitals in England over a six-month period and evaluation using the NHS AKI e-alert algorithm followed by recognition and management of AKI stages 1, 2 and 3 following random selection and review of a sub-set of patient case notes. Patients aged 29 days to 17 years were included. AKI stage 1 was defined as a rise of 1.5-<2x baseline creatinine level; AKI stage 2 a rise of 2-<3x baseline and AKI stage 3 a rise of >3x baseline. Urine output was not considered for AKI staging. Results: 57,278 creatinine measurements were analysed. 5325 (10.8%) AKI alerts were noted in 1112 patients with AKI 1 (62%), AKI 2 (16%) and AKI 3 (22%). There were 222 (20%) <1y, 432 (39%) 1-<6y, 192 (17%) 6-<11y, 207 (19%) 11-<16y and 59 (5%) 16-17y. Case notes of 123 of 1112 [11.1%] children with AKI alerts were reviewed. Confirmed AKI was recognised with a documented management plan following its identification in n=32 [26%] patients only. Conclusions: In this first multicentre study of the incidence of AKI in children admitted to selected hospitals across England, the incidence of AKI was 10.8% with most patients under the age of 6 years and with AKI stage 1. Recognition and management of AKI was seen in just over 25% children. These data highlight the need to improve recognition of AKI in hospitalised children in the UK.